(Re)Learning to Live Together in 2020 - Deardorff, Darla K. (Journal of International Students, 2020)
Ten years ago, the world was quite a different place with the devastation of a 7.0 magnitude earthquake in Haiti, the exuberance of the 2010 Winter Olympics in Vancouver, the release of the first iPad, the launch of Instagram, and the beginning of Arab Spring.  Fast forward to 2020 and not only is it the 10th anniversary of the Journal of International Students, but the world is facing unprecedented times with a global pandemic that has illustrated the interconnectedness of humankind like never before.  We have all been reminded of the power of human connection as we experience isolation, confinement, social distancing, and even fear.  We have witnessed powerful images of front-line workers giving their all, and neighbors in cities and towns across the world connecting from balconies and through windowpanes. These images have reminded us how much our lives depend on those around us, and how important it is that we renew our efforts in learning how to live together.